2021
DOI: 10.3390/nu13082537
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status of Children with Cerebral Palsy in Gorkha, Nepal: Findings from the Nepal Cerebral Palsy Register

Abstract: Background: The study aimed to define the burden and underlying risk factors of malnutrition among children with cerebral palsy (CP) in Gorkha district, Nepal. Methods: The first population-based register of children with CP in Gorkha, Nepal (i.e., Nepal CP Register—NCPR) was established in 2018. Children aged <18 years with confirmed CP were registered following standard protocol. Nutritional status was determined based on anthropometric measurements (height/length, weight, mid-upper-arm-circumference) fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 34 publications
3
14
0
1
Order By: Relevance
“…Such an evidence gap from LMICs where the majority of children with CP reside is concerning [ 11 ]. Considering the high burden of malnourished children with CP in LMICs [ 1 , 2 , 3 , 4 , 5 , 8 , 9 ], there is a dire need to reduce this evidence gap, and integration of nutrition interventions in the existing service plan for children with CP is essential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an evidence gap from LMICs where the majority of children with CP reside is concerning [ 11 ]. Considering the high burden of malnourished children with CP in LMICs [ 1 , 2 , 3 , 4 , 5 , 8 , 9 ], there is a dire need to reduce this evidence gap, and integration of nutrition interventions in the existing service plan for children with CP is essential.…”
Section: Discussionmentioning
confidence: 99%
“…Undernutrition is a major global public health challenge, and children with disability, such as cerebral palsy (CP), often suffer from undernutrition, especially in low- and middle-income countries (LMICs). The proportion of malnutrition is substantially higher among children with CP in LMICs compared to the general population [ 1 , 2 , 3 , 4 , 5 ]. Ensuring availability and accessibility to evidence-based nutrition interventions is essential to avert adverse outcomes of malnutrition among those vulnerable children [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Portugal, the omission rates are 53% for weight and 62.3% for height [ 29 ]. In a study from Nepal, the nutritional status information in national reports was also very limited and the authors say that this gap in evidence remains a major obstacle for planning targeted nutritional intervention for children with CP [ 28 ]. Thus, it is important to promote ways to improve the availability of this information.…”
Section: Discussionmentioning
confidence: 99%
“…National and other surveillance programs of children with CP provide clinical information [ 26 , 27 ] as well as nutritional status data. Countries that preform this analysis report elevated rates of undernutrition, but the most concerning is the higher underreport of anthropometric data [ 28 , 29 ]. To our knowledge, there is no record on the reasons why registers from the program do not always assess this evaluation parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to gather population-based data. Recently established population-based CP registries in two other LMICS, Bangladesh and Nepal, showed that more than two thirds of children were malnourished [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%